Trans-arterial embolization of acquired uterine arteriovenous malformation after Cesarean section: A case series - Achmad Kemal Harzif; OG (REI); Agrifa Haloho; Melisa Silvia; Gita Pratama; OG (REI); MRepSc; Yuditiya Purwosunu; OG (MFM); Ph.D; Aria Wibawa; OG (MFM); et al. (Shahid Sadoughi University of Medical Sciences, 2019)
Background Acquired uterine arteriovenous malformation (AVM) is a rare condition due to traumatic episodes in cesarean section. The patient can suffer from life-threatening hemorrhage or recurrent vaginal bleeding. Establishing this diagnosis is difficult, often misdiagnosed due to lack of information and number of cases. Trans-Arterial Embolization (TAE) procedure is rarely performed in our center. All of the cases were found with history of massive bleeding and diagnosed lately after recurrent bleeding history. Even though promising, one of our cases failed to be managed with TAE. It is important to diagnose early symptoms of AVM in order to prevent the life threatening event. Case presentation In these case series, four cases of AVMs after cesarean procedures will be reviewed. One could be diagnosed in less than a month but the other three took several months. The symptom of vaginal bleeding might occur a few weeks after the procedure is done, and most patients need transfusion and hospitalization. Three out of four patients were initially sent to the hospital in order to recover from shock condition, and one patient was sent for a diagnostic procedure. AVMs diagnostic was established with ultrasound with or without angiography. Three of our cases were succeeded by performing TAE procedure without further severe vaginal bleeding. One case failed to be treated with embolization and had to proceed with hysterectomy. Conclusion AVM should be considered early-on in patient with abnormal uterine bleeding and history of cesarean section. Embolization is still the first-choice treatment of AVMs, otherwise definitive treatment is hysterectomy in a patient without fertility need, or impossible to perform TAE.